DINAMIKA KONFLIK INTERPERSONAL DI LEMBAGA PENDIDIKAN ISLAM DAN STRATEGI PENGELOLAANNYA - Akhmad Khalwi Nawawi; Purodi Purodi (Universitas Islam Bunga Bangsa Cirebon, 2023)
Interpersonal conflict within Islamic educational institutions constitutes a persistent yet underexamined phenomenon that significantly affects organizational health, staff performance, and the quality of educational outcomes. Despite the normative expectation that Islamic educational environments should embody harmony and ukhuwah, empirical realities indicate that conflicts among educators, administrators, and other stakeholders remain prevalent and frequently mismanaged. This study investigates the dynamics of interpersonal conflict in Islamic educational institutions and the strategic approaches to their management, pursuing three specific objectives: (1) to analyze the typology and principal sources of interpersonal conflict in Islamic educational institutions, (2) to examine the impacts of unmanaged conflict on institutional effectiveness, and (3) to construct a conflict management model grounded in Islamic values of islah, adl, and hikmah. Employing a systematic library research methodology drawing on thirty-one peer-reviewed sources published between 2020 and 2025, the study proposes the Islamic Constructive Conflict Management (ICCM) model, a five-stage framework integrating contemporary conflict resolution principles with prophetic conflict management approaches. Implications for madrasah principals, Islamic educational administrators, and organizational development practitioners are elaborated.